1998
DOI: 10.1080/02844319850158985
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of the Face: The Safety of Narrow Excision Margins

Abstract: Recent studies have shown that narrower excision margins may be safe, but the optimal or minimum margin for melanoma is unknown. Wide margins of excision are possible on the trunk and limbs, but functional and cosmetic constraints often limit the extent of excision on the face. A collaborative study from two continents (Cape Town, South Africa and Northwood, England) investigated the outcome of different excision margins of 106 patients with stage I melanoma of the face. The margin of excision was measured fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
17
0
2
Order By: Relevance
“…Quoted 5-year survival figures for head and neck melanoma include 65%, 70%, 77%, 82%, 85% and 85% [5,7,10,23,[26][27][28], and quoted loco-regional recurrence rates include 12%, 15%, 19%, 20%, 23% and 27% [2,4,5,26,28,29]. Direct comparison between different studies however is hindered by variations in Breslow thickness for the different cohort populations [6,7,21,23,26,28,29]. Despite this, our figures would indicate that management of this disease remains sub-optimal, and this emphasises the need to optimise its management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quoted 5-year survival figures for head and neck melanoma include 65%, 70%, 77%, 82%, 85% and 85% [5,7,10,23,[26][27][28], and quoted loco-regional recurrence rates include 12%, 15%, 19%, 20%, 23% and 27% [2,4,5,26,28,29]. Direct comparison between different studies however is hindered by variations in Breslow thickness for the different cohort populations [6,7,21,23,26,28,29]. Despite this, our figures would indicate that management of this disease remains sub-optimal, and this emphasises the need to optimise its management.…”
Section: Discussionmentioning
confidence: 99%
“…compared to margins ranging from 11 to 70 mm (83% 5.y.s.). Similarly, Hudson et al [28] failed to account for tumour depth when they reported that, in 106 cases of clinical stage 1 facial melanoma, categorisation by excision margin (<1, 1-2 and >2 cm) failed to show statistically significant differences in long-term recurrence or survival (local recurrence, <1 cm 13%, 1-2 cm 14%, >2 cm 12%; melanoma-specific survival, <1 cm 92%, 1-2 cm 80%, >2 cm 66%). Thus, the results from both studies are difficult to apply clinically.…”
Section: Adherence To Guidelinesmentioning
confidence: 90%
See 1 more Smart Citation
“…This Level 1 evidence supports the recommendation that MIS can be removed with a 5‐mm margin. Four other studies involving MIS also presented convincing evidence that a 1‐cm margin or less is adequate 11–16 …”
Section: Evidence‐based Management For Patients With Melanoma ≤ 4 MMmentioning
confidence: 91%
“…Some evidence clearly indicates a surgical excision with a 1-cm margin is not much different from a 2-cm margin. [6][7][8][9][10][11][12][13][14][15][16] There are differing opinions concerning the excisional margins for melanoma in situ (MIS). Some authors advocate a minimum of 1-2 cm margin for MIS.…”
Section: ) Surgical Marginsmentioning
confidence: 99%